2007
DOI: 10.1080/09595230701247681
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous alcohol consumption and other barriers to antiviral treatment among hepatitis C positive people receiving opioid maintenance treatment

Abstract: Amongst people on opioid maintenance treatment (OMT), chronic hepatitis C (HCV) is common but infrequently treated. Numerous barriers, including misuse of alcohol may limit efforts at anti-viral treatment. The aim of this study was to define barriers, including alcohol misuse, to the effective treatment of HCV amongst OMT recipients. Ninety-four OMT patients completed the 3-item Alcohol Use Disorders Identification Test (AUDIT-C). A semi-structured interview was used in 53 subjects to assess alcohol use in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…Few studies, however, have investigated the influence of naltrexone on HIV treatment outcomes among patients prescribed ART [100], but data are beginning to emerge [101]. Since naltrexone appears to be safe in HIV-infected individuals [102-104] and in those with AUDs [105], naltrexone has the potential to improve ART adherence through reduction of alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies, however, have investigated the influence of naltrexone on HIV treatment outcomes among patients prescribed ART [100], but data are beginning to emerge [101]. Since naltrexone appears to be safe in HIV-infected individuals [102-104] and in those with AUDs [105], naltrexone has the potential to improve ART adherence through reduction of alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol also increases the risk of overdose when consumed with opioids (Warner-Smith, Darke, Lynskey, & Hall, 2001) and unsafe injecting and sexual behaviours (Rees, Saitz, Horton, & Samet, 2001;Stein et al, 2000). IDUs with alcohol problems are a potential target group for brief alcohol interventions, which have been successfully delivered in similar contexts such as opioid treatment (Watson et al, 2007). Further exploration of the role and outcomes of brief intervention in the IDU-targeted PHC setting may be warranted.…”
Section: Patterns Of Drug Usementioning
confidence: 98%
“…Although no additional benefi t was found in "facilitated" educational sessions focused on HCV and liver health compared with "standard" postdiagnostic counseling, these interventions resulted in an overall 22.7% reduction in drinking after 6 months, but there are no data available beyond this time point (Drumright et al, 2011). Other studies of HCV-positive IDUs refl ect the uncertainty of lasting declines in drinking following diagnosis (Stein et al, 2002;Watson et al, 2007), whereas Campbell and colleagues (2006) found high levels of problem drinking despite 84% of their sample reporting awareness of the increased risk of liver disease among HCV-positive individuals who continue to drink. Despite much research, however, the question has yet to be examined outside the context of major urban centers.…”
Section: T He Continued Spread Of Hepatitis C Virusmentioning
confidence: 99%